Making roub cheese - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
Trials in cheese-making using lactic acid (route or buttermilk) rather than imported rennet, which is forbidden to Muslims, have been successfully conducted among selected villagers and nomads m Sudan. The United Nations Development Programme Area...